PENGARUH KONSERVATISME, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Teguh Erawati; Dewi Kusuma Wardani; Afriyanti Hafil (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2022)
The purpose of this study is to prove the effect of conservatism, capital structure and liquidity on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study consisted of 21 companies after the selection through purposive sampling method. The research data uses secondary data, data in the form of documents or financial reports downloaded from www.idx.co.id. The research data were analyzed using multiple linear regression analysis. The results showed that conservatism had a positive effect on financial performance, capital structure had a positive effect on the company's financial performance and liquidity had a positive effect on the company's financial performance